Mergers and Acquisitions, Patents and R&D in the Pharmaceutical Industry During the COVID-19 Emergency - Mejía, Carlos Alberto (Sociedad y Economía, 2023)
This article describes global transformations and restructurings in the pharmaceutical industry related to mergers and acquisitions, patent policy and R&D in the context of the global emergence of COVID-19 and the search for a vaccine cure. A documentary analysis of cases and a literature review were carried out. The main findings seem to reveal a crisis of creativity and productivity in the sector about the discovery of new curative principles and the launch of new drugs. This situation is combined with increasing patent expiry and competition from generic companies. The emergence of the coronavirus and the very rapid development of vaccines for its cure or mitigation seem to have provided a new opportunity for this science-based branch of the industry.